Conductive coating, cation‐intercalation, and oxygen vacancies co‐modified vanadium oxides as high‐rate and stable cathodes for aqueous zinc‐ion batteries. Issue 4 (27th January 2023) - Tan, Shandong; Sang, Zhiyuan; Yi, Zhehan; Guo, Jingdong; Zhang, Xueqi; Li, Pinxiang; Si, WenPing; Liang, Ji; Hou, Feng
Abstract: Layered vanadium oxides are promising cathode materials for zinc‐ion batteries (ZIBs) owing to their high capacity, but the sluggish electron/ion migration kinetics and structural collapse/dissolution severely limit their Zn 2+ ‐storage performance. Herein, poly(3, 4‐ethylenedioxythiophene) coated and Mn 2+ ‐intercalated vanadium oxides with rich oxygen vacancies (MnVOH@PEDOT) are prepared as the cathodes for ZIBs. The PEDOT coating, synergistic with oxygen vacancies, tailors the electron conductivity, and the Mn 2+ ‐intercalation enlarges the interlayer spacing for rapid Zn 2+ ‐ions diffusion. In addition, the pre‐intercalated Mn 2+ ‐ions act as "pillars" to stabilize the structure, and the PEDOT coating prevents the direct contact of vanadium oxides with electrolyte to inhibit its dissolution during cycling. Thus, the MnVOH@PEDOT cathode exhibits superior discharge capacity, favorable rate capability (336.0 mAh g −1 at 8 A g −1 ), and satisfying cyclic durability (84.8% capacity retention over 2000 cycles). This work offers a facile and synergistic design strategy for achieving favorable cathodes for ZIBs. Abstract : The PEDOT coated and Mn 2+ ‐intercalated vanadium oxides with rich oxygen vacancies (MnVOH@PEDOT) are prepared by simple hydrothermal method. The PEDOT layer, synergistic with oxygen vacancies, accelerate the charge transfer, and the Mn 2+ ‐intercalation provides rapid ion diffusion. In addition, the PEDOT layers suppress its dissolution during cycling. Therefore, MnVOH@PEDOT delivers a high reversible capacity, superior rate capability and ultralong cycling stability.